A Comparative Study of Siswati Proverbs at Mjokwane and Manzolwandle High Schools: A Thematic Approach. (1st July 2016) - Thwala, J.J.
Abstract: The focus of this study is on Siswati proverbs that are compared and analysed according to their themes. Their explicit objectives on thematic exploration, origins, structural classification and functionality areevident. The specific themes that are randomly selected are marriage, parenthood, revenge, threat, unfaithfulness, deception, ingratitude, pride, fortune and friendship. Proverbs are regarded as a major vehicle for transmission ofbeliefs and values of society. They reflect the past, present and future of the society. It is further noted that theyare the significant oral expressions of culture that entail ideals, experiences, philosophy and wisdom of the nation.They reflect various themes, connotative and denotative meanings and figures of speech. Their intention ofpromoting social harmony and morality in society are ensured in everyday speech in different situations. Theirthematic exploration asserts language as a powerful tool that greatly influences on human lives. Both qualitativeand quantitative methods complement each other at various situations in this research article.